Penerapan Data Mining untuk Menganalisis Kepuasan Nasabah BPRS Al-Ma’soem Menggunakan Algoritma C4.5 - Dewi, Sofia; Salsabila, Jihan Salma; Aryanti, Utami (INTERNAL (Information System Journal), 2025)
Customer satisfaction levels with the services provided by BPRS Al Ma’soem Bandung using the C4.5 Customer satisfaction is an important factor in influencing the running of a bank. To understand the indicators that influence customer satisfaction, it is necessary to evaluate the level of customer satisfaction with a service. This article explains the use of the classification method with the C4.5 algorithm at BPRS Al Ma'soem Bandung. Data were obtained from 406 respondents through a questionnaire covering variables such as service, facilities, ease of access, products, and trust. The results of the analysis show that the attributes of trust and suitability have the greatest influence on customer satisfaction. The resulting model has an accuracy level of 96.31%, indicating the effectiveness of the C4.5 algorithm in analyzing data. This study provides recommendations to BPRS Al Ma'soem to improve service quality, adjust facilities, and products to customer needs to maintain competitiveness in the Islamic banking sector.